Lagenorhynchus albirostris - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
1. White-beaked Dolphin Lagenorhynchus albirostris French: Dauphin a bec blanc / German: Weil 3schnauzendelfin / Spanish: Delfin de hocico blanco Other common names: \White-beaked Porpoise, White-nosed Dolphin Taxonomy. Delphinus albirostris Gray, 1846, type locality unknown. Later designated by J. E. Gray in 1846 as “North Sea, coast of Norfolk,” England, UK, and further modified by Gray in 1850 to “Great Yarmouth.” Taxonomy of Lagenorhynchus is currently in dispute. Recent molecular analyses have revealed that the genus is not monophyletic. L. albirostris is the type species, but more recent molecular studies have shown that not all of the other members of the genus are close relatives, so those species will likely be placed into different genera sometime in the near future. L. albirostris may belong to an isolated lineage within Delphinidae. Monotypic. Distribution. Temperate to subarctic waters of the N Atlantic including S Davis Strait, Gulf of Saint Lawrence, Barents Sea, and North Sea, S to Cape Cod (USA) in the E and the coasts of N France in the W. Extralimital sightings in the Baltic Sea, Bay of Biscay, and Iberian Peninsula. Descriptive notes. Total length 240-310 cm; weight 180-350 kg. Neonates are 110-120 cm long and weigh c.40 kg. Male White-beaked Dolphins are slightly larger than females. The White-beaked Dolphin has a robust body shape more reminiscent of porpoises (Phocoenidae) than other delphinids (ocean dolphins), and a short beak only 5-8 cm long. Dorsal fin and flippers are long and falcate, with pointed tips. Upper flanks and back are black to dark gray, and belly and beak are white to pale gray. Most of the tailstock is pale mottled gray, and a pale gray streak extends anteriorly from this area onto upper flanks in front of dorsal fin. There may also be pale gray streaks around eyes. Dorsal fin, flukes, and flippers tend to be a uniform dark gray, and there may also be a black patch on the chest. There are 22-28 pairs of sharp, conical teeth in each jaw. Habitat. Throughout North ...